2022
DOI: 10.7306/gq.1640
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the trace fossil Megagrapton Książkiewicz, 1968 with focus on Megagrapton aequale Seilacher, 1977 from the lower Eocene of the Lesser Caucasus in Georgia

Abstract: Megagrapton Książkiewicz, 1968 is a characteristic deep-sea trace fossil belonging to the group of graphoglyptids and mostly preserved as a network of irregular meshes in hypichnial semirelief. So far, eleven ichnospecies have been distinguished under this ichnogenus, though commonly on weak evidence. The so-far poorly known ichnospecies Megagrapton aequale Seilacher, 1977 is described here on the basis of the numerous, newly discovered specimens from deep-sea siliciclastic deposits of the Bolevani Subsuite (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…2017; Uchman et al . 2022), however, only four bioturbation traces are undoubtedly produced by echinoids (Uchman 1995): Bichordites Plaziat & Mahmoudi, 1988, Scolicia Quatrefages, 1849, Cardioichnus Smith & Crimes, 1983 and Sursumichnus Uchman et al ., 2022. Additionally, de Gibert & Goldring (2008) analysed the taphonomic processes of trace fossils produced by echinoids and suggested that the producers of Bolonia Meunier, 1886 were irregular echinoids.…”
mentioning
confidence: 99%
“…2017; Uchman et al . 2022), however, only four bioturbation traces are undoubtedly produced by echinoids (Uchman 1995): Bichordites Plaziat & Mahmoudi, 1988, Scolicia Quatrefages, 1849, Cardioichnus Smith & Crimes, 1983 and Sursumichnus Uchman et al ., 2022. Additionally, de Gibert & Goldring (2008) analysed the taphonomic processes of trace fossils produced by echinoids and suggested that the producers of Bolonia Meunier, 1886 were irregular echinoids.…”
mentioning
confidence: 99%